Effect of organic additives on the mitigation of volatility of 1-nitro-3,3 `-dinitroazetidine (TNAZ): next generation powerful melt cast able high energy material - Talawar, M. B.; Singh, Alok; Naik, N. H.; Polke, B. G.; Gore, G. M.; Asthana, S. N.; Gandhe, B. R. (Journal of Hazardous Materials, 2006)
1-Nitro-3,3'-dinitroazetidine(TNAZ) was synthesized based on the lines of reported method. Thermolysis studies on synthesized and characterized TNAZ using differential scanning calorimetry (DSC) and hyphenated TG-FT-IR techniques were undertaken to generate data on decomposition pattern. FF-IR of decomposition products of TNAZ revealed the evolution of oxides of nitrogen and HCN containing species suggesting the cleavage of C/N-NO(2) bond accompanied with the collapse of ring structure. The effect of incorporation of 15% additives namely, 3-amino-1,2,4-triazole(AT), 3,5-diamino-1,2,4-triazole (DAT), carbohydrazide (CHZ), 5,7-dinitrobenzofuroxan (DNBF), bis (2,2-dinitropropyl) succinate (BNPS), triaminoguanidinium nitrate (TAGN), 2,4,6-trinitrobenzoic acid (TNBA) and nitroguanidine (NQ) on the volatility of TNAZ was investigated by undertaking thermogravimetric analysis. The TG pattern brings out the potential of BNPS and TAGN as additives to mitigate the volatility of TNAZ. The influence of additives on thermal decomposition of pattern of TNAZ was also investigated by DSC. The DSC results indicated that the additives did not have appreciable effect on the melting point of TNAZ. Scanning electron microscopic (SEM) studies were carried out to investigate the effect of additives on morphology of TNAZ. This paper also discusses the possible mechanism involved in between the TNAZ and TAGN and BNPS. It appears that the formation of charge transfer complex formation between the TNAZ and TAGN/BNPS. The effect of addition of high explosives such as CL-20, HMX and RDX on thermo-physical characteristics of TNAZ is also reported in this paper. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: melt castable explosive; morphological structure; synthesis; Thermolysis; trinitroazetidine (TNAZ); volatility behavior

Examining the compatibility of energetic plasticizer DNDA-5 with energetic binders - Vijayalakshmi, R.; Agawane, N. T.; Talawar, M. B.; Khan, Md Abdul Shafeeuulla (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2020)
The requirement of developing energetic binders with suitable energetic plasticizers is to enhance the mechanical properties and to reduce glass transition temperature of propellant and explosive formulations. Compatibility of energetic plasticizer 2,4-dinitro-2,4-diazapentane (DNDA-5) with four different energetic binders viz. poly glycidyl nitrate (PGN), poly(3-nitratomethyl-3-methyloxetane) (PLN), glycidyl azide polymer (GAP) and tetra functional glycidyl azide polymer (t-GAP) was studied by using differential scanning calorimeter (DSC) and density functional theory (DFT) methods. Results obtained for the pure binder was compared with the results obtained for binder/plasticizer blend in the parameters of decomposition temperature and the format of the peak which indicated the compatibility or incompatibility of DNDA-5 with the studied binders. Glass transition temperatures of all these blends were determined by low temperature DSC and showed desirable lowering of glass transition temperature with single peak in the case of PLN. The proposed energetic plasticizer DNDA-5 has displayed its compatibility with three binders PGN, PLN and GAP employing thermal techniques. DNDA-5 has been found as incompatible when it is mixed with t-GAP. The predicted relative trend of interaction energies between plasticizer and binder has provided concurrence to results drawn from thermal studies.
Keywords: Computational study; DNDA-5; Glass transition temperature; plasticizing effect; thermal